Kritik Sastra Feminisme dalam Cerpen Luh Sekar lan Satuané Rikala Ujané Bales Tusing Dadi Tanggehang - Ramadhana, Muhamad Rizky Rafli; Rai Putra, Ida Bagus; Antara, Nala (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2025)
This research focuses on analyzing the female characters in Putu Supartika's short story, "Luh Sekar lan Satuané Rikala Ujané Bales Tusing Dadi Tanggehang." This story contains numerous aspects of feminist discourse, interwoven with social critique of related phenomena in Balinese society. The data analysis was conducted using two primary methods, beginning with structural literary analysis. The findings indicate that the short story "Luh Sekar lan Satuané Rikala Ujané Bales Tusing Dadi Tanggehang" explores the theme of a father's cruelty, where the characters Luh Sekar and her Mother consistently experience situations that violate norms and their rights as women. The story features three characters and their distinct personalities, set primarily in a house, a room, and a community health center (Puskesmas), and employs a linear plot progression. Subsequently, the literary work was analyzed using feminist literary theory. The research findings related to the female characters reveal various elements of feminism. Relevant sentences, paragraphs, and dialogue excerpts were collected and thoroughly examined through the lens of feminist literary criticism.